Fabrication of Aligner Removal Tool. Issue 3 (July 2021) - Ram, RSVM Raghu; Ranganayakulu, I; Viswanadh, K Anand
Firm adaptation and locking of the thermoplastic aligners, retainers, and bleaching trays make it difficult during removal, making the patients often frustrated, leading to poor compliance. Generally, to remove these, patients tend to use their fingernails or some sharp hooks, which would cause distortion or a tear. Hence, a simple, user-friendly aligner removal tool was designed to overcome these issues.